The EFFECT OF SOCIAL MEDIA MARKETING ON PURCHASE INTENTIONS WITH BRAND AWARENESS AND PERCEIVED QUALITY AS INTERVENING VARIABLES AT ASTON BELLEVUE RADIO DALAM HOTEL IN JAKARTA - Anjarani, Puti Minang; Mumin, Adhi Trirachmadi; Bilqis, Linda Desafitri Ratu; Ingkadijaya, Rahmat (Bina Nusantara University, 2023)
Social media plays a role in adding value to the attractiveness of two-way communication between companies and their consumers so as to increase consumer closeness to certain brands or brands. The ASTON Bellevue Radio Dalam hotel uses social media Facebook and Instagram as a marketing tool to introduce the ASTON Bellevue Radio Dalam brand to the public. At the beginning of the establishment of the ASTON Bellevue Radio Dalam hotel, the use of social media was still not actively used. In addition, at the beginning of its establishment, the ASTON Bellevue Radio Dalam hotel was also affected by the Covid-19 pandemic, resulting in a significant decrease in occupancy rates. Hotel ASTON Bellevue Radio Dalam is pursuing various strategies including increasing the amount of social media marketing activity to market and promote Hotel ASTON Bellevue Radio Dalam. The use of social media marketing also allows consumers to have an image and perception of the good quality of the ASTON Bellevue Radio Dalam hotel. The purpose of this study was to analyze social media marketing on purchase intention with brand awareness and perceived quality as intervening variables at the ASTON Bellevue Radio Dalam hotel, Jakarta. According to the research that has been done, it is known that social media marketing directly has a significant influence on brand awareness, perceived quality, and purchase intention. In this study it can also be seen that brand awareness directly has a significant effect on purchase intention and perceived quality directly has a significant effect on purchase intention. However, on the results of testing the direct effect of the relationship between variables, it is known that the results of brand awareness have no significant effect on perceived quality. In testing the indirect effect, brand awareness as a mediating variable indirectly has a significant effect and has a relationship between social media marketing and purchase intention. In addition, it is also known that perceived quality as a mediating variable indirectly has a significant effect and has a relationship between social media marketing and purchase intention.